Analysis of Student Problems in Learning Fiqh Mawaris in Higher Education - Sintya Nur Zahrawani; Arhamdah Arhamdah; Sri Dwi Khoironi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
The phenomenon that occurs to students is their difficulty in detailing and sorting out the division of inheritance. This material is indeed difficult to understand, especially in the details of each received by the heirs. This study aims to find out what problems occur in students of Islamic religious education regarding Islamic jurisprudence. This study uses a qualitative method with a case study approach. Sources of data were taken from five informants through in-depth interviews who were selected using techniques of purposive sampling, all informants are active students majoring in Islamic religious education at Universitas Negeri Padang in 2019 and 2020. The results of the analysis show that there are three problems that occur with Islamic religious education students regarding Fiqh Mawaris. These three problems are i) the difficulty of determining the parts that must be received by the heirs, ii) the lack of time allocation used in the rose material and the lack of understanding of mathematical concepts, and iii) students' lack of mastery and repetition of the rose material. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.